Pengaruh Stock Selection Skill, Market Timing Ability, Dan Fund Age Terhadap Kinerja Reksa Dana Saham Dengan Fund Cash Flow Sebagai Variabel Intervening Pada Perusahaan Yang Terdaftar Di Otoritas Jasa Keuangan Periode 2016 – 2020 - Kafita Dewi; Andini Nurwulandari (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to examine the effect of stock selection skills, market timing capabilities, and age of funds on the performance of equity mutual funds through the cash flow of funds as an intervention variable in companies registered with the Financial Services Authority for the period 2016 – 2020. The sample selection technique uses purposive sampling with a total sample of 20 types of equity mutual funds consisting of 11 companies in a period of 5 years so that the total sample obtained is 100 samples that meet the criteria. The method of data analysis in this study is Structural Equation Modeling (SEM) which was carried out with the help of the AMOS 22 program. The results of research on the performance of equity funds indicate that directly stock selection skills and fund age have a positive and significant effect on the performance of stock mutual funds, market timing ability does not directly affect the performance of equity funds. While the results of research on the cash flow of funds indicate that stock selection skills and age of funds directly have a positive and significant effect on the performance of cash flows of funds, the ability of market timing does not directly affect the cash flow of funds. The results of the research indirectly indicate that the variables of stock selection skills, market time capabilities, and age of funds affect the performance of equity funds through the cash flow of funds as an intervention variable.